2006
DOI: 10.1038/sj.ejcn.1602518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hazelnut-enriched diet on plasma cholesterol and lipoprotein profiles in hypercholesterolemic adult men

Abstract: Objective: Frequent consumption of nuts is associated with favorable plasma lipid profiles and reduced risk of coronary heart disease (CHD). This study was conducted to investigate the effects of hazelnut-enriched diet on plasma cholesterol and lipoprotein profiles in hypercholesterolemic adult men compared with baseline and control diet, and also to measure the anthropometric parameters, habitual physical activities, nutrient intake and endothelial function. Subjects and design: Fifteen hypercholesterolemic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 56 publications
(77 reference statements)
6
82
0
1
Order By: Relevance
“…Previous research on hazelnut supplementation has been limited to three studies. The results from this study strengthen the findings of previous smaller intervention trials that have shown similar improvements in blood lipid concentrations with the consumption of hazelnuts (Alphan et al, 1997;Durak et al, 1999;Mercanligil et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous research on hazelnut supplementation has been limited to three studies. The results from this study strengthen the findings of previous smaller intervention trials that have shown similar improvements in blood lipid concentrations with the consumption of hazelnuts (Alphan et al, 1997;Durak et al, 1999;Mercanligil et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…To date, only three short-term intervention trials have assessed the effects of hazelnut supplementation on blood lipids (Alphan et al, 1997;Durak et al, 1999;Mercanligil et al, 2007). However, the sample size used in all three studies was relatively small and one of the studies was a poorly designed, non-randomized trial using a convenience sample (Durak et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…P. Borges, Carvalho, Correia, and Silva, 2007;De Vasconcelos, Bennett, Rosa, and Ferreira-Cardoso, 2010 (nut) § Low-fat content § Protective effect against CVD § Good lipid profile, mainly PUFA and followed by MUFA. § Antioxidant properties § Important amounts folates, thiamin and riboflavin § Electrolite balance contribution § Important source of phenolic compounds § Glucorregulation properties § Lactose-free; low available carbohydrate § Prebiotic effect § Cholesterol-free § Possible contribution in protection against some cancers, such as colon cancer § High digestibility § Suitable for celiacs and lactose intolerants § Low GI § Low Na content Alasalvar, Shahidi, Liyanapathirana, and Ohshima, 2003;Durak et al, 1999;Koksal, Artik, Simsek, and Gunes, 2006;Li et al, 2009;Mercanligil et al, 2007;Ozdemir et al, 2001, Tey et al, 2011 § Good lipid profile, mainly MUFA. § Protective effect against CVD § Important amounts of niacin, Vit.B1, Vit.B2, Vit.B6 and ascorbic acid.…”
Section: Discussionmentioning
confidence: 99%
“…No presente estudo piloto observou-se uma diminuição do Colesterol Total e LDL-C ao se comparar seus valores médios basais e após oito semanas de intervenção. O período desse estudo baseou-se em outros ensaios clínicos mostrando que esse tempo é sufi ciente para confi rmar o efeito hipolipemiante (Ballesteros et al, 2001;Rodrigues et al, 2003;Praça et al, 2004;Behall et al, 2004;Mercanligil et al, 2007).…”
Section: Discussionunclassified